Do interactions between formal and informal institutions matter for productive entrepreneurship? - Godlewska, Małgorzata (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: Institutional and Entrepreneurship theory pays attention to institutions and their influence on productive, unproductive and destructive entrepreneurship in transition economies. However, according to the literature, it is not only institutions that matter for productive entrepreneurship, but also the interaction between formal and informal institutions. Moreover, transition economies needs the productive entrepreneurship ‘to catch-up’ with world leaders. Aim: The aim of this paper is to advance institutional research through the development of a better understanding of the relation between formal and informal institutions and their influence on productive entrepreneurship in transition economies like CEECs. Results: The paper demonstrates that strong formal and informal institutions, the ‘invisible hand’ of the state, as well as the complementary and accommodating relations between formal and informal institutions are necessary for productive entrepreneurship in transition economies.